Complicated skin and soft tissue infection with Mycobacterium fortuitum following excision of a sebaceous cyst in Taiwan - Tsai, Shih-Chen; Chen, Li-Hsin; Liao, Hsien-Hua; Chiang, Chih-Yu; Lin, Wea-Lung; Chen, Shiuan-Chih; Tsao, Shih-Ming; Hung, Hung-Chang; Lee, Yuan-Ti (The Journal of Infection in Developing Countries, 2016)
Mycobacterium fortuitum group (M. fortuitum), also known as rapidly growing Mycobacteria, can cause pyogenic infections in human beings, most commonly in immunocompromised patients. Herein, we present a 40-year-old immunocompetent male patient who underwent planned excision of a sebaceous cyst in the abdominal wall. He suffered from tender erythematous lesions with purulent discharge around the healing wound that developed 2 weeks after surgery. Gram stain, bacterial and fungal culture results of the wound were negative. A diagnosis of non-tuberculous mycobacteria was made from a wound culture from the area of operative debridement, which was subsequently confirmed to be M. fortuitum group using PCR-restriction fragment length polymorphism analysis of the hsp65 gene. The patient received 4 weeks of parenteral imipenem/cilastatin 500 mg every 6 hours and amikacin 500 mg every 12 hours, plus oral clarithromycin 500 mg twice daily, and the wound recovered completely. He was discharged and followed up regularly at our outpatient clinic, and continued taking oral ciprofloxacin and clarithromycin 500 mg twice daily for 6 months. This case highlights the importance of strict aseptic precautions even during minor procedures, and also the characteristics of M. fortuitum infections in immunocompetent patients, which usually develop as localized postsurgical wound infections. We also share our experience in successfully treating a M. fortuitum complicated skin and soft tissue infection.